ANALISIS KEBUTUHAN BAHAN AJAR FLIPBOOK BERBANTUAN HEYZINE MATERI BANGUN DATAR UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR - Destiani; Mansur, Nabilah; Kamil, Nurdin; Nurani, Dwi Cahaya; Astika, Ruri Tria; Najwa, Wulida Arina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the need for developing a Heyzine-assisted digital flipbook teaching material on the topic of plane figures to enhance the learning outcomes of fifth-grade students in elementary school. The method used is a descriptive qualitative approach through observation, interviews, and documentation. The results of the study indicate that learning is still dominated by the lecture method, learning resources are less varied, and students require more interactive visualization to comprehend concepts in learning. Teachers and students need digital teaching materials that are engaging, easily accessible, and compliant with the Merdeka Curriculum. The Heyzine-assisted digital flipbook is deemed appropriate because it can present text, images, and videos interactively, thereby increasing understanding and learning motivation, accompanied by an improvement in learning outcomes. Therefore, the development of a digital flipbook is highly necessary as a solution for more effective and relevant mathematics learning.